Analisis Korelasi dan Kointegrasi Indeks Pasar Saham Utama Dunia dan IDX Tahun 2013 - 2019 - Pristina Hermastuti Setianingrum; Doddi Prastuti (Jurnal Manajemen, 2022)
The Indonesia Stock Exchange (IDX) is one of the fastest growing capital markets. The relatively large proportion of foreign investment in the IDX is expected to cause a high frequency of inflows and outflows of funds from the IDX. There is a possibility that the inflows and outflows of the IDX will move to the stock exchanges of other countries which provide better profit opportunities. This study is to find out how big the correlation and cointegration of the world's major stock market indices, namely the European stock market represented by the London stock market (FTSE-100), the American stock market represented by the New York stock market (DJI), the Asian stock market represented by stock market in Singapore (STI) and Hong Kong (HKEX) against the composite stock price index on the Indonesia Stock Exchange (IDX). The conclusions obtained are (i) there is a positive (weak to moderate) and significant correlation between FTSE-100 with IDX, DJI with IDX, STI with IDX and HKEX with IDX, (ii) there is cointegration between FTSE-100 with IDX, DJI with IDX , STI with IDX and HKEX with IDX. Cointegration between the IDX composite stock price index and the stock market index in four other countries minimizes the possibility for investors to gain arbitrage profits by investing in foreign exchanges. (iii) FTSE-100, DJI, STI, HKEX and IDX do not have a unit root test, this means that the data in period t-1 does not affect the data in period t. This also means that the stock market in this study is a random walk.